Implementasi Metode Snowball Throwing untuk Meningkatkan Self Confidence Siswa pada Pelajaran SKI Kelas VIII MTs Tanwiriyah Kalisari Bojonegoro - Aulia Nailul Izzati Sasabila; Hurin Innihayatus Sa'adah (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
The low level of student self-confidence within the context of active learning remains a significant challenge in the current Indonesian education landscape. Based on various national education reports and psychological studies, it has been found that many students feel awkward, fear making mistakes, and lack confidence in their abilities when asked to perform or express opinions in class. This phenomenon indicates a need for learning methods that focus not only on cognition but also on fostering character growth, particularly self-confidence. This study aims to determine how the implementation of the Snowball Throwing-based cooperative learning method improves students' self-confidence in Islamic Cultural History (SKI) subjects, specifically focusing on: (1) belief in one's own abilities, and (2) courage in expressing opinions and taking responsibility. This research employs a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The research subjects were the teacher and students of class VIII-2 at MTs Tanwiriyah Kalisari. The results show that the application of the Snowball Throwing method significantly enhances student self-confidence. Students became more certain of their abilities, more active in expressing opinions, and demonstrated the courage to make decisions and take responsibility during the learning process. These findings align with Lauster’s indicators of self-confidence, which emphasize the importance of self-expression, decision-making, and belief in personal competence. Furthermore, these results support Jean Piaget’s constructivism theory, where students actively build understanding through direct experience, social interaction, and reflection on the challenges they face.